Pengaruh Foot And Hand Massage Therapy Terhadap Penurunan Intensitas Nyeri Pada Ibu Post Sectio Caesarea - Dian Mya Mariyana; Yuni Astuti; Rusnaningish (An-Najat, 2024)
Postpartum women with caesarean section experience post-surgical pain. Post-cesarean section pain has a negative impact on the patient's health, reduces the patient's comfort level, inhibits bonding between mother and baby, interferes with daily activities (ADL) and inhibits early initiation of breastfeeding (IMD). This study aims to determine the effect of foot and hand massage therapy in reducing pain intensity in mothers after caesarean section. The research method used is descriptive and based on a nursing case study approach. The research subjects, post-cesarean section patients, experienced moderate pain (scale 4 to 6). The research instruments were a questionnaire observation sheet, PQRST pain assessment and Numeric Rating Scale (NRS) pain measurement. The research was conducted for 2 days post sc on May 17 2024 to May 20 2024 with implementation once a day for 20 minutes. After 3 days of intervention, the pain scale decreased to scale 2 with NRS measurements and PQRST assessment. Conclusion: based on foot and hand massage carried out for 3 days, it shows that foot and hand massage therapy has a significant effect on reducing pain intensity in mothers after cesarean surgery. The application of non-pharmacological therapy can be used for post-cesarean mothers to reduce post-cesarean pain